Innovative Design of an Effective E-Commerce Web Model for Optimizing the Distribution of Agricultural Products in Rural Areas - Surya Danang; Durand Fernandito Freddy Setlight; Fricy O. Rumintja (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Objectives: This study aims to identify the key distribution barriers faced by farmers, develop an appropriate e-commerce model, and analyze the primary factors influencing the adoption of digital platforms in Sinsingon Village, North Sulawesi. Methodology: A survey of 75 farmers was conducted to capture distribution challenges and adoption readiness. The data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression to examine the relationships between six independent variables perceived ease of use, perceived usefulness, digital literacy, social support, internet infrastructure, and electricity infrastructure and farmers’ intention to adopt digital platforms. Findings: The study identified five major distribution barriers: the absence of a digital marketing platform, dependency on middlemen, inadequate storage facilities, weak bargaining power, and limited access to accurate price information. The majority of respondents (79%) favored a Business-to-Business (B2B) e-commerce model due to its efficiency in handling bulk transactions and institutional buyers. Regression results indicated that all variables significantly influenced adoption intention, with an explanatory power of R² = 0.74. The most influential factor was perceived usefulness (β = 0.38), followed by perceived ease of use (β = 0.29), social support (β = 0.26), internet infrastructure (β = 0.24), digital literacy (β = 0.21), and electricity infrastructure (β = 0.19). Conclusion: The findings confirm the applicability of the Technology Acceptance Model (TAM) and underscore that successful adoption requires not only technical readiness but also socio-economic integration. This study offers a conceptual blueprint for a B2B agricultural e-commerce system tailored to rural contexts, with the potential to improve efficiency, inclusivity, and sustainability in agricultural distribution.